Mandatory contrast-enhanced venography to detect deep-vein thrombosis (DVT) in studies of DVT prophylaxis: upsides and downsides - Hirsh, Jack; Ginsberg, Jeffrey S.; Chan, Noel; Guyatt, Gordon; Eikelboom, John W. (Thrombosis and Haemostasis, 2014)
The introduction of venography into patient care was a major advance because it was the first accurate method for the diagnosis of DVT. Compression ultrasound has since become the preferred test for patients with suspected DVT because, unlike venography, it is simple, non-invasive and widely available. Venography has facilitated the development and approval of new anticoagulants and remains widely used as an efficacy outcome in trials of venous thromboembolism prevention. Most thrombi detected by screening venography are, however, small and unimportant for patients. In order to calculate the trade-off between an asymptomatic thrombus and a bleed we require an estimate of the number of asymptomatic thrombi that must be prevented to avoid a patient-important thrombus. A credible estimate of this ratio is not available. Therefore when used as a measure of efficacy in trials of thromboprophylaxis, venography has limitations for comparing the relative effects of alternative antithrombotic agents on outcomes important to patients.
Keywords: Deep-vein thrombosis; venous thrombosis; prophylaxis